Pheidole iceni n. sp. (hymenoptera: formicidae), a new ant for an old institution (2011)
Pheidole iceni a new species of ant (Formicidae: Myrmicinae) is described based on soldiers and workers from Chocó, Colombia. The ant is named in honor of the Instituto de Ciencias Naturales of the National University of Colombia in its 75th anniversary